lectronic and transport properties of graphene decorated with alkali metals (Li and K) - Vaca Chanatasig, Cristina Magdalena (2022)
A study of the effects of the adsorption of alkali metals in the transport properties of graphene, taking all the possible sites of adsorption, is essential to understand the storage mechanisms in carbon-based materials. In this work, we propose the analysis of the electronic and transport properties of graphene on alkali metals, Li and K, such as bands, density of states, and conductance. The configurations analyzed here are: a) Top site (on top of a carbon atom of the sublattice A of graphene), b) Hollow site (adatom in the center of the graphene hexagons), and c) Bridge site (adsorbate atom in the middle of the A-B bridge of the graphene carbon atoms). With this aim, we will use a tight binding Hamiltonian model for orbitals of graphene perturbed by the interaction with Li and K in the three mentioned inequivalent configurations. Then, we use the Green's function equation of motion method to calculate the corresponding band structures and density of states. The numerical calculations to obtain the quantum conductance are performed with kwant, the quantum simulation package of python. We find that the bands are up or down shifted with respect to pristine graphene, indicating doping with electrons. For the Top and Bridge cases, the AB symmetry breaking produced in this configuration generates small bandgaps. The bands of the Hollow sites show a downshifting of the Fermi level and preserve the Dirac cones nature from the pristine graphene. Finally, the perturbation of the Fermi velocities observed in the bands is translated to the V-shaped conductance.